2019
DOI: 10.1002/wat2.1366
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the decision‐making behavior of irrigators

Abstract: The contribution of agriculture to society is undeniable, as is its impact on the environment. Irrigators' decisions to follow best management practices or implement a policy change, to accept a technology, or even to exit farming, all affect society. Hence the decision-making behavior of irrigators is of interest to politicians, policymakers, and researchers due to their impact on resource use and social concerns for their welfare. There are numerous studies available regarding the decision-making behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 173 publications
0
6
0
Order By: Relevance
“…Zeng et al (2017) used SVM to analyze the competitive or complementary relationship between reservoir operation decisions for hydroelectricity production and water releases for irrigation. Another potential venue of applying machine learning for knowledge discovery is mining relations that cannot be modeled from a physical process-based perspective such as the two-way feedback between human and water systems (Meempatta et al, 2019;Pande & Sivapalan, 2017). Interpretable machine learning algorithms such as tree-based methods and Lasso hold promise for this purpose because the learned models can be interpreted to derive rules or F I G U R E 9 Observed and simulated daily streamflow at USGS Gage 13340600 for two water years.…”
Section: Mining Relationships Among Hydrologic Variables For Knowledge Discoverymentioning
confidence: 99%
“…Zeng et al (2017) used SVM to analyze the competitive or complementary relationship between reservoir operation decisions for hydroelectricity production and water releases for irrigation. Another potential venue of applying machine learning for knowledge discovery is mining relations that cannot be modeled from a physical process-based perspective such as the two-way feedback between human and water systems (Meempatta et al, 2019;Pande & Sivapalan, 2017). Interpretable machine learning algorithms such as tree-based methods and Lasso hold promise for this purpose because the learned models can be interpreted to derive rules or F I G U R E 9 Observed and simulated daily streamflow at USGS Gage 13340600 for two water years.…”
Section: Mining Relationships Among Hydrologic Variables For Knowledge Discoverymentioning
confidence: 99%
“…improve yield and change irrigation type). These goals were most likely to be linked to maximising profitability but also being able to plan ahead for different scenarios on and off-farm (Alcon et al , 2014; Meempatta et al , 2019).…”
Section: Need For Data Integration For Scenario-based Planning: An Analogous Case Of Water-related Risk and Decision-makingmentioning
confidence: 99%
“…Indeed, systems that ignore expert users' needs and knowledge can result in failure to provide the management improvements desired (Desouza, 2003) especially for SAMPJ small-to medium-sized enterprises which typically comprise farming (Desouza and Awazu, 2006). From an in-depth review of 310 key irrigation journal articles, Meempatta et al (2019) found key irrigation decisions to be able to be grouped across time frame. This includes decisions that are daily (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to temporal scale, scholars have differentiated between the timing of action relative to a stimulus, such as drought, and the duration of response. The timing of action relevant to the stimulus has been described as proactive, concurrent, or reactive, while the duration of response has been characterized as tactical, strategic, or structural (e.g., Meempatta et al 2019;Risbey et al 1999;Smit et al 2000). In the drought management literature, reactive and proactive actions have been used interchangeably with crisis and risk management actions, respectively (e.g., Cai et al 2015;Wilhite 2017Wilhite , 2000Wilhite et al 2000).…”
Section: Existing Typologies Of Climate Change and Drought Adaptation And Barriers To Adaptationmentioning
confidence: 99%